NITROSELULOSA DARI KULIT BATANG PISANG - Satibi, Loekman (BRIN Publishing, 2005)
This paper describes the manufacturing of nitrocellulose from the bark of banana tree as a model of the manufacturing from other sources of cellulose in general. The process can be devided into two steps. The fisrt step is the production of cellulose from the bark of banana tree by coustic soda process while in the second step the cellulose obtained then subjected to nitration procces using nitric acid and controlled by addition of sulfuric acid. In the fisrt step dry bark of banana tree digested using coustic soda solution. Coustic soda concentration, the weight ratio of coustic soda solution to dry bark of banana tree, and digestion time were taken as process variables. The results of the fisrt step concludes that the highest cellulose yields is 33,36 percent, obtained at the digestion operating condition of NaOH concentration 3,33 percent, ratio of NaOH solution to dry bark of banana tree 12per1 and digestion time 4,5 hours and permanganate number is 17,27, while the lowest permanganate number of cellulose is 14,40 in accord with almost the lowest yield 26,58 percent obtained at the digestion process condition of NaOH concentration 5 percent, ratio of NaOH solution to dry bark of banana tree 12per1 and digestion time 4,5 hours. These results are almost in accord with the prediction. The second step operation will be accomplished after the completion of the equipments. Sulfuric acid solution is used to control nitration process based on the third Le Chatelier chemical principle.